Dietary supplementation of encapsulated anthocyanin loaded-chitosan nanoparticles attenuates hyperlipidemic aberrations in male Wistar rats - P.R. Sreerekha (Carbohydrate Polymer Technologies and Applications, 2021)
Our previous studies have demonstrated that the physico-chemical and structural properties of encapsulated anthocyanin loaded chitosan nanoparticles (ACNPs) have potential in vitro antioxidant properties. The study explores the hypolipidemic effect and mechanism of dietary supplementation of ACNPs in male Wistar rats, fed on experimental high fat-alcohol diets. The ACNPs treated group has significantly higher catalase and superoxide dismutase (SOD) enzyme activity levels (p > 0.05). The supplementation with ACNPs significantly reduced the serum total cholesterol and triglycerides levels. The lipid-mediated oxidative stress and lipid levels in serum and liver were reduced too. The western blotting experiments revealed normalization of the fatty acid synthase (FAS), and HMGCR (Hydroxymethylglutaryl Co-A reductase) activities after supplementation with ACNPs. The study concludes that the ACNPs are promising functional dietary supplement with definite hypolipidemic activity.